Kajian Dasar Teknik Kursi Kosong untuk Praktisi Bimbingan dan Konseling - Ira Septi Sulistiana; Illa Rohillah; Rakha Razeva Abhipraya; Imalatul Khairat (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
The empty chair technique is an intervention method rooted in Gestalt therapy, where clients are encouraged to engage in symbolic dialogue with a part of themselves or with a significant figure connected to their emotional experience. Through this imaginative dialogue, clients are able to express suppressed feelings, recognize internal conflicts, and develop new awareness of the issues they are facing. This article aims to provide a foundational review of the empty chair technique for guidance and counseling practitioners, especially those seeking to deepen their understanding and skill in applying the technique with accuracy and empathy. The discussion includes the definition of the empty chair technique, its core objectives in the counseling process, practical implementation steps, as well as its potential effectiveness and limitations in various counseling settings, both individual and group. It is expected that this article will serve as an initial reference to equip practitioners with a comprehensive understanding before applying the technique in professional practice. Furthermore, the humanistic orientation of the technique reinforces essential counseling values such as empathy, full presence, and respect for clients’ subjective experiences, all of which are vital to building a healing and supportive therapeutic relationship.